2014
DOI: 10.7567/apex.7.113003
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of domain wall evolution at a bifurcation in magnetic network structures

Abstract: We report on the magnetization dynamics at a bifurcation in a dual-branch magnetic network structure. When a transverse domain wall (DW) propagates through the network, interaction with an edge defect at the bifurcation leads to the transformation of the DW from transverse to vortex. The topological charge is conserved as the DW moves through the bifurcation, and this charge conservation is intrinsically linked to a %1/2 topological defect in the system. Magnetic force microscopy (MFM) imaging enables the dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…Phusp et al 25 demonstrated the topological dependence for a vortex DW trajectory and we have recently shown that the same principle applies for a TDW moving through a Y-shaped structure35. As such, we note that for a +½ ∼ −½ TDW flowing through a branch structure, the conservation of the topological defect will lead the TDW to move along the upper edge of a Y shape structure.…”
Section: Resultssupporting
confidence: 65%
“…Phusp et al 25 demonstrated the topological dependence for a vortex DW trajectory and we have recently shown that the same principle applies for a TDW moving through a Y-shaped structure35. As such, we note that for a +½ ∼ −½ TDW flowing through a branch structure, the conservation of the topological defect will lead the TDW to move along the upper edge of a Y shape structure.…”
Section: Resultssupporting
confidence: 65%
“…in symmetric structure, the DW experiences similar potential barriers along the UHR and LHR. The motion of the DW is determined by the arrangement of the topological edge defects making it chirality dependent 20 21 22 . However, when we introduce an offset at the bifurcation, the potential barriers experienced by the DW are different in both directions.…”
Section: Resultsmentioning
confidence: 99%
“…The circular pad is used for nucleating and injecting a DW into the longitudinal nanowire. A 6-μm-long and 100-nm-wide transverse nanowire is positioned at a distance of 1 μm from the output branch to assign chirality to the injected DW 12 18 . When the magnetization of the transverse nanowire is aligned along the + y direction, the injected DW attains an ACW chirality, conversely, a CW chirality DW is injected if the magnetization is aligned along the − y direction.…”
Section: Resultsmentioning
confidence: 99%
“…The selective switching was ascribed to the arrangement of topological edge charges of DW at the bifurcation of the network structure 11 . We previously reported selective trajectory of a transverse DW (TDW) in Y-shaped branch structure via a complex interaction of edge defects with the vertex at the bifurcation 12 . The above observations have direct application in the formation of 1D Dirac strings in an artificial spin ice lattice 2 11 .…”
mentioning
confidence: 99%